A novel gastric release PEG‐enclatherated polymethacrylate‐based memblet system. Issue 6 (25th October 2012) - Cooppan, Shivaan; Choonara, Yahya E.; du Toit, Lisa C.; Kumar, Pradeep; Ndesendo, Valence M.K.; Pillay, Viness
Abstract A novel polymethacrylate‐based membranous system referred to as a "memblet" was developed for potential application in controlled gastric drug delivery. A polymethacrylate‐based latex, Eudragit® E100, was enclatherated with a 60% w/v and a 30% w/v solution of polyethylene glycol 4000 to form hydrogel formulations A and B, respectively. The hydrogels were subsequently compressed into memblets that were characterized for thermal, rheological, morphological, mechano‐chemical properties, and in vitro gastric drug release analysis. Molecular mechanics (MM) simulations were performed to corroborate the experimental findings. Critical yield values of 15.39 and 5.239 Pa were obtained for hydrogel A and B, respectively. The viscoelastic region was found to be <10.67 and 2.542 Pa for hydrogels A and B, respectively. The storage modulus was greater than the loss modulus for hydrogel A while the inverse was true for hydrogel B. Thermal, mechanical, and surface morphology evaluation revealed that the converse was true for the dried membrane structure with hydrogel B having superior characterization profiles than hydrogel A. Notably, the lower PEG concentration (30% w/v) displayed better characterization profiles than a higher concentration (60% w/v). Through MM simulations, desirable agreement between the theoretical and experimental results was achieved over the given concentration range of PEG. Based on the gastric drug release analysis, memblets formulated with hydrogel B displayed superior control of drug release. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013